Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2015)
2,3-Dihydroxynaphthalene forms 2:1 cocrystals with its p-ditoluate and 1:1 cocrystals with its m-ditoluate but not with the o-ditoluate. In 2:1 cocrystals of the p-ditoluate, naphthalene diol molecules form a dimeric motif through OH...O hydrogen bonding interactions. The adjacent dimers sandwich the molecules of p-ditoluate through C-H...pi interactions. In 1:1 cocrystals of the m-ditoluate, naphthalene diol molecules generate a zigzag pattern through O-H...O hydrogen bonding interaction involving -OH of the diol and the C=O of the m-ditoluate. Intermolecular toluoyl group transfer reaction was more facile in cocrystals of the p-ditoluate as compared to cocrystals of the m-ditoluate. This difference in reactivity is consistent with the relative geometry of the electrophile (El, C-O) and the nucleophile (Nu, OH) in these cocrystals. A comparison of the cocrystallization behavior and structure of the two cocrystals with their constituents suggests that the position of the methyl group is crucial for cocrystal formation. A survey of the CSD revealed that the incidence of polymorphism and cocrystals formation decreases (number of hits) in the order para- > ortho- > meta- for disubstituted benzene derivatives. This suggests that compounds prone to exhibit polymorphism have more propensities to form cocrystals as compared to those that resist polymorphism. This information could be useful while selecting cocrystal formers and construction of supramolecular functional assemblies with desired properties.